1999
DOI: 10.1097/00007632-199907010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the Chest Cage and Spine During Breathing in Healthy Individuals and in Patients With Adolescent Idiopathic Scoliosis

Abstract: The range of movement of the chest cage and spine is more limited in the scoliotic cases. This overall stiffness of the chest cage and the spine may contribute to the mechanical inefficiency and impairment of pulmonary function found in scoliotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 14 publications
2
54
0
Order By: Relevance
“…The motion restriction found in our study can be interpreted in several different ways. First, as reported by several authors, it could be due to the 3D structural changes of spine [9,19,21,22,30], pelvis [15,29,32], and hip components [3,37,38], which provide a clinically observed stiffness of the human body. However, we did not have any hypothesis for the hip transversal restriction, except as a consequence of the prolonged contraction of the GM and S muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The motion restriction found in our study can be interpreted in several different ways. First, as reported by several authors, it could be due to the 3D structural changes of spine [9,19,21,22,30], pelvis [15,29,32], and hip components [3,37,38], which provide a clinically observed stiffness of the human body. However, we did not have any hypothesis for the hip transversal restriction, except as a consequence of the prolonged contraction of the GM and S muscles.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that displacement of the ventral part of the rib cage during quiet breathing primarily occurred in the anteroposterior and craniocaudal directions. 19 Leong et al 16 showed that the mean displacements of thoracic and abdominal markers were greater in the craniocaudal direction than in other directions during deep breathing. We think that measuring only unidirectional displacements would be insufficient for assessments of breathing movements for various breathing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is limited to measuring the anteroposterior diameters of breathing movements. Although several previous studies have assessed the 3-dimensional motions of the thorax and abdomen during breathing using infrared cameras 15,16 and an electromagnetic device, 17 there is no reported literature on the 3-dimensional distances of the observational points on the thorax and abdomen during breathing.…”
Section: Introductionmentioning
confidence: 99%
“…he scoliotic spinal deformity of lateral flexion and rotation of the involved vertebrae around a vertical axis and the attached ribs causes chest cage stiffness, reduced hemidiaphragmatic movement, and uneven distribution of the inhaled air on the concave side resulting in a decrease in pulmonary function [1][2][3] . The effect of surgical correction on the pulmonary function of patients with adolescent idiopathic scoliosis is controversial.…”
mentioning
confidence: 99%